Algebraic aspects of digital communications - Shaska, Tony, 1967-; Hasimaj, Engjell (NATO science for peace and security series., 2009)
Focuses on connections between algebra, algebraic geometry, number theory, graph theory and related areas of mathematics with coding theory and cryptography. This title is suitable for mathematicians, computer scientists and engineers who need to explore ties between algebra and coding theory and cryptography.